OPTIMIZATION OF WATER RESOURCES THROUGH THE IMPLEMENTATION OF A MONITORING SYSTEM BASED ON THE USE OF IOT TECHNOLOGY - LIZANA-ALCALDE, DAYLEN (2024)
THE CONSTANT CLIMATE CHANGE THAT HAS OCCURRED IN RECENT YEARS AND A CONSIDERABLE POPULATION GROWTH IN PERU IS HAVING A SIGNIFICANT IMPACT ON WATER RESOURCES, WHICH IS WHY IT IS OF INTEREST TO OPTIMIZE WATER RESOURCES, THIS CAN BE ACHIEVED BY IMPLEMENTING A MONITORING SYSTEM FOR WATER RESOURCES, TAKING INTO ACCOUNT THAT IT SEEKS TO BETTER MANAGE THE AVAILABLE WATER RESOURCES. IN THIS SENSE THE IOT TECHNOLOGY, AS A TOOL, CAN PROVIDE US WITH THE ACCESSES TO PERFORM. TAKING INTO ACCOUNT THE USE OF IOT TOOL WE CAN COLLECT IMPORTANT INFORMATION ON WATER RESOURCES, ALL THIS INFORMATION CAN BE VIEWED FROM ANYWHERE IN THE WORLD IN REAL TIME, WITH WHICH WE CAN MANAGE IN AN APPROPRIATE MANNER; WHICH WOULD OPTIMIZE VARIOUS AREAS, MAINLY THAT OF POPULATIONS THAT SCARCE WATER RESOURCES, ALL THIS WITH A SYSTEM THAT INVOLVES PLC THAT MANAGES THE INFORMATION AND ESPECIALLY THAT ALLOWS US TO INTERCONNECT TO THE CLOUD, AND ONCE THE INFORMATION IN THE CLOUD, IT CAN BE VIEWED AND MONITORED FROM ANYWHERE IN THE WORLD. © 2024 IEEE.